The effects of mixing air distribution and heat load arrangement on the performance of ceiling radiant panels under cooling mode of operation. (3rd October 2017) - Mustakallio, Panu; Kosonen, Risto; Melikov, Arsen
Abstract : The cooling power of radiant panels can be effected by the arrangement of heat loads and by the room air distribution system. This impact can be important because often the cooling output is the critical factor for the design and usability of radiant panels. In this study, the impact of heat load arrangement and air distribution generated in a room by linear slot diffuser, radial multi-nozzle diffuser and radial swirl induction unit on the cooling power of radiant panels was compared. The impact on the thermal environment was also studied. Measurements were carried out without and with supply air in a test chamber equipped with two ceiling radiant panels and air distribution units flush with the radiant panels. The heat load was generated through the walls and with heated cylinders. The cooling power of the radiant panels was increased with the studied air distribution methods. The increase was from 5% to 17% depending on the air distribution method and the heat load arrangement. The most significant effect of the heat load arrangement occured when heat loads are located unevenly and their convection flow turns or weakens the supply air jet flushing the radiant panels.